(untitled) (The Pakistan Development Review, 2002)
Irrigation water shortages have lately been a main area of concern for policymakers and planners in Pakistan. Current literature on the country’s water resources predicts an alarming situation regarding the availability of irrigation water in the future due to declining water tables and serious financial, environmental, and social constraints of developing big storage reservoirs. Since there is little room to augment water supplies by building new dams, the existing supply-driven surface irrigation system needs to be replaced by a demand-based system with special focus on water use efficiency through the introduction of an appropriate water pricing system. The present study aims to evaluate several alternative water pricing systems in the search for choosing one that will ensure efficient use of irrigation water in Pakistan. A related objective is to test the extent of sensitivity of the demand for irrigation water to a change in alternative water prices. A major conclusion that emerges from this research is that irrigation water shortages are the result of the inflexibility of the present irrigation water supply system for agricultural use and have little to do with the existing water pricing practice in the country. Furthermore, the results of our water price simulations exercise confirm the general perception that demand for irrigation water is less sensitive to changes in alternative irrigation water prices. Two findings from the pricing policy perspective are: (i) irrigation water is not available in adequate quantity to farmers in the nine sub-districts surveyed at almost all of the alternative prices in Pakistan’s irrigated agriculture sector since the predicted water usage at all prices is greater than the actual usage for all districts; and (ii) our empirical analysis indicates significant inefficiency of resource allocation in respect of irrigation water as shown by its positively large marginal value product to opportunity cost ratio.